Analysis of Warehouse Activities Through System Application Product (Sap) to Monitor Target Percentage of Order Fulfillment Finished Good Warehouse of PT XYZ - Asti, Maulyta Wira (Asian Journal of Logistics Management, 2024)
The global recession that occurred in America had an impact on the decline in the value of exports of Indonesian textiles and textile products. PT. XYZ is a multinational company that has been affected by the global recession due to a decrease in product demand in the international market. Research shows that there is one factor in Order Fulfillment's non-achievement caused by reduction in the number of order customer requirements on goods produced by PT. XYZ. The research aims to determine the inhibiting factors of not achieving the OFF performance target, information regarding the implementation of SAP warehousing, SAP has a very crucial role in supporting the smooth running of the company's activities as a whole including warehouse activities from upstream to downstream, the process receiving until complete shipment process product to customer. Knowing the process flow of warehouse operation of activities finished goods and the role of SAP for OFF monitoring as Key Performance Indicator Finished Goods Warehouse department PT. XYZ. The author uses a descriptive approach by qualitative methods. The research results obtained several internal and external factors such as sewing damage, missing order quantity, missing scanning output, material shortage and other factors affecting the failure to achieve OFF as a work KPI indicator which in its implementation is influenced by inhibiting processes so that OFF does not reach its target. OFF is a measure of the company's ability to fulfill the number of order requests exactly according to the requests and requirements put forward by each customer.